PENGARUH COUNTRY OF ORIGIN, MEREK, DAN HARGA PADA NIAT BELI KONSUMEN PRODUK MOBIL DI YOGYAKARTA - Harjanti, Sri (Jurnal Bulletin, 2018)
Effect of Country of Origin, Brand, and Prices for Buying Consumers Car Products in Yogyakarta. This research examines how the influence of Country of origin, Brand and price on the intention to buy consumers. The sample determination method uses non probability sampling by convenience sampling. The sample in this study is that there are 150 consumers of car products in Yogyakarta. Data collection uses survey methods using a questionnaire. The results showed that the Country of origin and brand have a partial effect on the consumer's purchase intention, while the price does not affect the consumer's purchase intention. Simultaneously, Country of origin, Brand and price affect the purchase intention of consumers